Time to full effect, following treatment with combined oral contraceptives (cyclic versus continuous administration) in patients with endometriosis after laparoscopic surgery: a prospective cohort study. (1st January 2022) - Triantafyllidou, Olga; Kolovos, Georgios; Voros, Charalambos; Vlachos, Athanasios; Vakas, Panagiotis; Vlahos, Nikos
Abstract: The risk of recurrence after surgery is a major problem in women who are suffering from endometriosis. The prescription oral contraceptives (OCs) in the treatment of endometriosis-related pain, in women who do not desire fertility, is still controversial. The aim of this prospective cohort study is to evaluate the time until the reduction in the mean intensity of dysmenorrhoea and deep dyspareunia takes effect, for patients who use combined OCs in the accepted cyclic manner, versus in the continuous fashion as after the laparoscopic excision of endometriosis. A total of 28 patients diagnosed with endometriosis who underwent surgical treatment were offered at least a 12 months course of oral contraceptives. The intensity of both symptoms was reduced at the end of observational period in both groups. The use of continuous OCs (11 patients) was associated with a more pronounced reduction in the mean intensity of dyspareunia and dysmenorrhoea at 9 ( p = 0.004) and 6 ( p = 0.003) months respectively as compared to the cyclic group (17 patients).